2021
DOI: 10.1016/j.ijhcs.2021.102603
|View full text |Cite
|
Sign up to set email alerts
|

Experimenters' Influence on Mental-Imagery based Brain-Computer Interface User Training

Abstract: Motor Imagery based Brain-Computer Interfaces (MI-BCIs) enable their users to interact with digital technologies, e.g., neuroprosthesis, by performing motor imagery tasks only, e.g., imagining hand movements, while their brain activity is recorded. To control MI-BCIs, users must train to control their brain activity. During such training, experimenters have a fundamental role, e.g., they motivate participants. However, their influence had never been formally assessed for MI-BCI user training. In other fields, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 46 publications
0
47
0
1
Order By: Relevance
“…In addition, differences in gender performances might have been prevailing because all experimenters in the current experiment were females. While Roc et al (2019) suggested that female experimenters might positively influence subjects' performance, Pillette et al (2021), using the same data, reported that the evolution of MI-BCI performance is dependent on the interaction between experimenters' and subjects' gender as well as subjects' tension level and that it cannot be firmly said that female experimenters benefit all subjects. This is while Wood and Kober (2018) found that female participants trained by female experimenters performed significantly worse than those trained by male experimenters.…”
Section: Fundamental Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, differences in gender performances might have been prevailing because all experimenters in the current experiment were females. While Roc et al (2019) suggested that female experimenters might positively influence subjects' performance, Pillette et al (2021), using the same data, reported that the evolution of MI-BCI performance is dependent on the interaction between experimenters' and subjects' gender as well as subjects' tension level and that it cannot be firmly said that female experimenters benefit all subjects. This is while Wood and Kober (2018) found that female participants trained by female experimenters performed significantly worse than those trained by male experimenters.…”
Section: Fundamental Characteristicsmentioning
confidence: 98%
“…Fundamental user characteristics were reported by Randolph (2012), who showed that females are likely to be better performers than males. Additionally, the effect of gender is shown to be modulated by that of the experimenter (Wood and Kober, 2018;Roc et al, 2019;Pillette et al, 2021). Other fundamental characteristics include age, which was reported to influence performance (Randolph et al, 2010) and the dominant hand of the user (Zapała et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For the exploratory phase, we used the standard "Graz BCI" bar feedback (Pfurtscheller and Neuper, 2001), as implemented in OpenViBE for 2-class MT-BCIs and as used in, e.g., Roc et al, 2019;Pillette et al, 2021. In that phase each run included 20 trials for each of the two MT classes. A classifier was built on the data from the two first runs to provide online feedback for the subsequent training runs of that session.…”
Section: Bci Protocolmentioning
confidence: 99%
“…Also, the influence of the participants' tension on MI-BCI performances seems to be modulated by the gender of the experimenter, which can be considered as a complex type of social presence and emotional feedback. Tensed and non tensed participants had better performances when training with men experimenters and women experimenters, respectively [33].…”
Section: Influence Of the Participants' Profile On Bci User Trainingmentioning
confidence: 97%